Pengaruh Senam Ergonomik Terhadap Penurunan Nyeri Dismenorea pada Remaja Putri - Elisa Sa'bania; Besse Lidia (Jurnal Kesehatan Komunitas, 2026)
Adolescence is a transitional period marked by physical and hormonal changes, including the maturation of the reproductive system. One of the health problems frequently experienced by adolescent girls is dysmenorrhea, which can disrupt learning activities and quality of life. This study aims to analyze the effect of ergonomic exercises on reducing dysmenorrhea pain in adolescent girls at SMPN 11 Samarinda. The study used a quasi-experimental pretest–posttest design. The sample consisted of 30 adolescent girls aged 12–15 years who experienced dysmenorrhea, divided into control and intervention groups. The intervention group received ergonomic and dysmenorrhea exercises, while the control group received only dysmenorrhea exercises. Pain was measured using a Visual Analog Scale before and after the intervention. Data analysis used the Mann-Whitney U Test and the Wilcoxon Signed Rank Test. The results showed a significant reduction in dysmenorrhea pain in both groups, with p < 0.05, and a greater reduction in pain in the intervention group. The study concludes that ergonomic exercises reduce dysmenorrhea pain.